2004
DOI: 10.1073/pnas.0306533101
|View full text |Cite
|
Sign up to set email alerts
|

In vitro synthesis of fully functional EmrE, a multidrug transporter, and study of its oligomeric state

Abstract: EmrE is a small multidrug transporter from Escherichia coli that provides a unique model for the study of polytopic membrane proteins. Here, we show its synthesis in a cell-free system in a fully functional form. The detergent-solubilized protein binds substrates with high affinity and, when reconstituted into proteoliposomes, transports substrate in a ⌬ H ؉ -dependent fashion. Here, we used the cell-free system to study the oligomeric properties of EmrE. EmrE functions as an oligomer, but the size of the func… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
103
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
4
1

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(109 citation statements)
references
References 26 publications
6
103
0
Order By: Relevance
“…Studies have shown that the basic functional unit of EmrE is an oligomer, as would be expected for a membrane protein of its small size. It appears established that the basic functional unit of EmrE is a homodimer, as shown by oligomerization assays, substrate binding experiments, negative dominance studies, and crosslinking analyses (3)(4)(5)(6)(7)(8). This conclusion is further supported by the existence of paired SMR proteins, such as YdgE/YdgF of E. coli, and EbrA/EbrB and YkkC/YkkD of Bacillus subtilis.…”
mentioning
confidence: 82%
“…Studies have shown that the basic functional unit of EmrE is an oligomer, as would be expected for a membrane protein of its small size. It appears established that the basic functional unit of EmrE is a homodimer, as shown by oligomerization assays, substrate binding experiments, negative dominance studies, and crosslinking analyses (3)(4)(5)(6)(7)(8). This conclusion is further supported by the existence of paired SMR proteins, such as YdgE/YdgF of E. coli, and EbrA/EbrB and YkkC/YkkD of Bacillus subtilis.…”
mentioning
confidence: 82%
“…This enabled unambiguous chemical shift assignment and simplified data interpretation. The capability of E. coli-based cell-free transcription and translation systems to express wild type EmrE in a functional form with and without detergent was previously shown (17,35). Furthermore, it has been reported that amino acid selective isotope labeling without dilution or scrambling is possible (34).…”
Section: Generalmentioning
confidence: 99%
“…Not all detergents are suitable for the refolding step but dodecylymaltoside (DDM), dodecylphosphocholine and lyso-phosphoglycerol derivatives (LMPG, LPPG) have been shown to successfully solubilize precipitates [55]. This approach has been successfully applied to the production of EmrE, a multidrug transporter [55,56], and to the human histamine-1 receptor [57]. Second, the addition of detergent directly to is that the membrane protein will be produced in a "native-like" environment which is necessary to obtain a functional protein.…”
Section: / Cell-free Membrane Protein Expressionmentioning
confidence: 99%